Microstructure properties of HVOF-sprayed NiCrBSi/WCCo-based composite coatings on AISI 1040 steel - Islak, Serkan; Buytoz, Soner (Natl Inst Optoelectronics, 2013)
NiCrBSi/WCCo-based composite coatings were produced on the surface of AISI 1040 steel using high velocity oxygen fuel (HVOF) thermal spraying technique. In the coatings produced, the WCCo quantity added to the NiCrBSi was chosen as 10, 30 and 50 wt. % percentages. The coatings were compared in terms of their phase composition, microstructure, and hardness. Phase composition and microstructure of the coatings were characterised using X-ray diffraction and scanning electron microscopy. The results indicated that the as-prepared NiCrBSi/WCCo-based composite coatings were mainly composed of Upsilon-Ni, WC, W2C, Cr23C6, Cr7C3, CrB2, CrSi, and Co phases. Microhardness values of coating layer varied according to the addition of the powder. The highest microhardness value of the coating was measured as 1300 HV0.2.
Keywords: HVOF; NiCrBSi; WCCo; Microstructure